2005
DOI: 10.1038/sj.gene.6364221
|View full text |Cite
|
Sign up to set email alerts
|

Chronic periodontal disease is associated with single-nucleotide polymorphisms of the human TLR-4 gene

Abstract: Periodontitis is an inflammatory disease affecting the connective tissue surrounding the teeth leading to tooth loss. Pathogens associated with periodontitis interact with Toll-like receptors (TLRs) to induce cytokines causing and aggravating disease. We screened 197 individuals suffering from generalized periodontitis for the presence of Asp299Gly and Thr399Ile of TLR-4 as well as Arg753Gln of TLR-2 in comparison to matched controls. Single-nucleotide polymorphisms (SNPs) of TLR-4 were elevated among patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
115
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 30 publications
9
115
2
7
Order By: Relevance
“…For TLR-4, two cosegregating SNPs (Asp299Gly and Thr399Ile) were associated with hyporesponsiveness to inhalation of LPS, the major ligand of TLR-4 (21). In subsequent studies, these SNPs were found to be associated, i.e., with infections caused by Gram-negative bacteria or with periodontitis (22,23). The Arg677Trp polymorphism of TLR-2 was found to be associated with lepromatous leprosy in a Korean population (24), and with tuberculosis in a Tunisian population (25).…”
mentioning
confidence: 98%
“…For TLR-4, two cosegregating SNPs (Asp299Gly and Thr399Ile) were associated with hyporesponsiveness to inhalation of LPS, the major ligand of TLR-4 (21). In subsequent studies, these SNPs were found to be associated, i.e., with infections caused by Gram-negative bacteria or with periodontitis (22,23). The Arg677Trp polymorphism of TLR-2 was found to be associated with lepromatous leprosy in a Korean population (24), and with tuberculosis in a Tunisian population (25).…”
mentioning
confidence: 98%
“…Single nucleotide polymorphisms (SNPs) in TLRs have been correlated with disease conditions such as asthma, endotoxin hyporesponsiveness, sepsis, immunodeficiencies, and atherosclerosis (11)(12)(13)(14)(15)(16)(17)(18). For TLR3, SNP P554S within LRR20 is linked with partial penetrance of herpes simplex virus-associated encephalitis in children (19).…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%
“…Some reports have shown that TLR-2, TLR-4 and the related signalling pathway play an important role in the initial recognition of T. cruzi and may regulate the initial pro-inflammatory response during infection with the parasite but may also contribute to the severity of the disease (Almeida & Gazzinelli 2001). Genetic variations in TLR genes correlate with several infectious diseases (Schroder et al 2005). Several single-nucleotide polymorphism (SNPs) have been described for the TLR2 and TLR4 genes.…”
mentioning
confidence: 99%
“…Genetic variations in TLR genes correlate with several infectious diseases (Schroder et al 2005). Several single-nucleotide polymorphism (SNPs) have been described for the TLR2 and TLR4 genes.…”
mentioning
confidence: 99%